Recent advance in treatment of osteoarthritis by bioactive components from herbal medicine - Xu-zhao Li; Shuai-nan Zhang (BMC, 2020)
Abstract Osteoarthritis (OA) is a common chronic articular degenerative disease, and characterized by articular cartilage degradation, synovial inflammation/immunity, and subchondral bone lesion, etc. The disease affects 2-6% of the population around the world, and its prevalence rises with age and exceeds 40% in people over 70. Recently, increasing interest has been devoted to the treatment or prevention of OA by herbal medicines. In this paper, the herbal compounds with anti-OA activities were reviewed, and the cheminformatics tools were used to predict their drug-likeness properties and pharmacokinetic parameters. A total of 43 herbal compounds were analyzed, which mainly target the damaged joints (e.g. cartilage, subchondral bone, and synovium, etc.) and circulatory system to improve the pathogenesis of OA. Through cheminformatics analysis, over half of these compounds have good drug-likeness properties, and the pharmacokinetic behavior of these components still needs to be further optimized, which is conducive to the enhancement in their drug-likeness properties. Most of the compounds can be an alternative and valuable source for anti-OA drug discovery, which may be worthy of further investigation and development.